PENGARUH STRETCHING TERHADAP KELUHAN MUSKULOSKELETAL PADA PERAWAT - Susi Mardi Lestari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Nurses to be one of medical staff who active role to increase health development. Nurse works to care giver in category manual material handling is job uses human energy, then nurse has the highest risk to musculoskeletal disorders. This research aimed to know the effect of stretching to musculoskeletal disorders among nurses in Ratna and Medical Surgical Room at Sanglah Hospital. This research was pre eksperimental design by one group pre-test post-posttest design. The total samples are 54 for total sampling. Each responden be given nordic body map kuesioner to count musculoskeletal disorders before and after stretching. Analysis techniques which use d to test was Wilcoxon with significancy level at 5% or p value = 0,05. The result of research among stretching to musculoskeletal disorders showed that p value < 0,05 is 0,000. It shows that can be stated there was significant effect of stretching to muskulosketela disorders among nurses in Ratna and Medical Surgical at Sanglah Hospital. Based on the result of this research will be basis for stretching to decrease musculoskeletal disorders so that increase health and fitness for nurses.